2022
DOI: 10.1088/2053-1591/ac639e
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing imprecise graphene foam resistance data

Abstract: 3D graphene foam is the main aim of this research work. Graphene foam is synthesized on the Ni-foam by the CVD technique. The graphene foam has been characterized by XRD, FESEM, Raman spectroscopy and BET techniques. The resistance of graphene foam with a variance of temperature has been measured through an LCR meter and has been analyzed with classical and neutrosophic analysis. As a result, it is seen that graphene foam is expressing both conductor and semiconductor electric properties and also it is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…For the analysis of the interval data, the classical average or mean formula is used. Generally, it is seen that most researchers have used the classical average for interval data as can be seen in our previous research work, 17 , 18 which is as follows Here, X L is the minimum/lower value and X U is the maximum/upper value of the interval. However, the neutrosophic one is more generalized than the classical method; it deals with indeterminacy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the analysis of the interval data, the classical average or mean formula is used. Generally, it is seen that most researchers have used the classical average for interval data as can be seen in our previous research work, 17 , 18 which is as follows Here, X L is the minimum/lower value and X U is the maximum/upper value of the interval. However, the neutrosophic one is more generalized than the classical method; it deals with indeterminacy.…”
Section: Resultsmentioning
confidence: 99%
“…The first thing observed from Figure a,b is that the capacitance of the tactile sensor increases and the resistance decreases as the applied force increases. Moreover, the difference from the combined graphs of the classical and neutrosophic analysis can be seen in Table . ,, From the graphs, it is easily observed that neutrosophic statistics is the generalization of classical statistics, as the classical graphs fall in the middle of the neutrosophic graphs. Also, the neutrosophic graph is much more reliable in making decisions and in concluding the solution of the problem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why the use of this approach has gained importance for the variance analysis of different problems in several fields, e.g. medicine, 29 applied sciences, 30 astrophysics 31 and material statistics like resistance and capacitance analysis, 32–34 etc. Moreover, the neutrosophic technique is more helpful than classical techniques; see the following references for examples.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first time that a controlled chamber with an LCR meter was used to measure the data of temperature sensors. Similarly, we used the classical and neutrosophic methods to analyze the measured data for resistance with respect to the change in the temperature of sensors (we have already used the classical and neutrosophic methods to analyze the resistance data of conductors 25 and 3D graphenes 30 with respect to the change in temperature).…”
Section: Introductionmentioning
confidence: 99%